The impact of interest rate strategies implemented by the central bank of the republic of Türkiye on the liquidity risk within the banking sector: An exploration using a nonlinear boundary test method - Sezal, Levent (Journal of Social Economics Research, 2024)
This study analyses the effects of changes in the CBRT’s policy interest rate on the liquidity adequacy ratio of the Turkish banking sector. In order to determine the relationships between variables, Lee and Strazicich unit root tests, which also take into account structural breaks, are applied. Accordingly, the asymmetric effect of the policy interest rates of the Central Bank of the Republic of Türkiye on the Turkish banking sector liquidity adequacy ratio is analysed with the Nonlinear Lag Distributed Autoregressive Model (NARDL). The ‘Toda-Yamamoto’ method, in the form of binary analysis, tests the direction of causality to determine if there is a causal relationship between the variables. According to the NARDL test results, no cointegration relationship was found between the CBRT policy interest rates and the Turkish banking sector. Conversely, the results of the causality test reveal a unidirectional causal relationship between policy interest rates and the liquidity adequacy ratio. As a result, the management of liquidity-related risks by banks is critical for the continuity of the bank’s operations. A change in the policy rate directly affects banks’ funding and funding ratios through money market rates, which in turn affects the emergence of liquidity-related risks in the short and long term. Proper management of liquidity-related risks could potentially lead to bank liquidation.